Male Internet pornography consumers and their attitudes toward men and women. - Burns, Ryan Joseph. (My University, 2001)
Grounded in pornography literature from the conservative-moralist, liberal, and feminist perspectives, and utilizing traditional theories of media effects, this study examined habitual male consumers of Internet pornography and their attitudes and beliefs about men and women. Two hundred sixty-five (N = 265) men completed an online survey that measured their perceptions of women in sexual, feminine and negative terms, their traditional attitudes about women, their perceptions of men performing traditional masculine behaviors increases, and their adherence to a masculine gender role schemata. Results revealed that men who habitually consume high amounts of Internet pornography are more likely to describe women in sexual terms, view women in stereotypically traditional feminine gender roles, and perceive them in positive terms. Also, habitual consumers perceive a world inhabited by masculine men, and report the highest level of self-perceived possession of masculine personality characteristics. Findings are discussed in terms of existing media effects theories, and suggestions for future research are presented.
Keywords: Sex role Public opinion.; Mass Communications.; Men Sexual behavior.; Internet pornography Social aspects.; Women Public opinion.; Information Science.; Male consumers Attitudes.; Psychology, Social.; Speech Communication.